2019
DOI: 10.3390/nano9030472
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Persistent Organic Pollutants and ZnO NPs in Synthetic and Natural Waters

Abstract: The use of zinc oxide nanoparticles (ZnO NPs) and polybrominated diphenyl ethers (PBDPEs) in different products and applications leads to the likelihood of their co-occurrence in the aquatic system, making it important to study the effect of PBDPEs on the fate and transport of ZnO NPs. In this study, we determine the influence of PBDPEs (BDPE-47 and BDPE-209) on the colloidal stability and physicochemical properties of ZnO NPs in different aqueous matrices. The results indicated the shift in ζ potential of ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Recent studies have reported the following: Adsorption of polybrominated diphenyl ethers on titanium dioxide and zinc oxide nanoparticles through aromatic ether groups and Br suppresses the agglomeration of nanoparticles in natural water resulting in enhanced transport and exposure of pollutants to aquatic organisms [ 227 , 228 ]. Sorption of certain antibiotics like levofloxacin and ciprofloxacin on graphene oxide (GO) enhances the mobility and transport of these antibiotics through porous media which may increase their risks to ecological receptors and could also cause groundwater contamination [ 229 ].…”
Section: Nanomaterials As Vectors For Other Contaminantsmentioning
confidence: 99%
“…Recent studies have reported the following: Adsorption of polybrominated diphenyl ethers on titanium dioxide and zinc oxide nanoparticles through aromatic ether groups and Br suppresses the agglomeration of nanoparticles in natural water resulting in enhanced transport and exposure of pollutants to aquatic organisms [ 227 , 228 ]. Sorption of certain antibiotics like levofloxacin and ciprofloxacin on graphene oxide (GO) enhances the mobility and transport of these antibiotics through porous media which may increase their risks to ecological receptors and could also cause groundwater contamination [ 229 ].…”
Section: Nanomaterials As Vectors For Other Contaminantsmentioning
confidence: 99%
“…Studies have shown that they are capable of increasing mortality of aquatic lives [9], damage DNA and induce neurotoxicity in bivalves [10,11], which are strong indications why they must be removed from water systems [12]. Previous researches have shown that microplastics can adsorb other contaminants in water when they come in contact with some of these cocontaminants in water includes metals [13,14], pharmaceuticals and personal care products [15,16] and other organic pollutants [17]. Other studies have shown the presence of microplastics in air [18], food [19], surface waters [20], soils [21], drinking water [13] and sediments [22].…”
Section: Introductionmentioning
confidence: 99%
“…The ingestion of microplastic, besides causing the obstruction of digestive tract, can facilitate the transfer of contaminants adsorbed by the plastic, with unclear consequences to the health of aquatic organisms and humans [5,6,7]. Indeed a major problem with microplastic is their ability to adsorb other common environmental contaminants, such as metals [8,9,10], pharmaceuticals [11,12], personal care products [12] and others [13,14]. Consequently, the microplastic can potentially cause diseases such as cancer, a malformation in animals and humans, impaired reproductive activity, and reduced immune response [15].…”
Section: Introductionmentioning
confidence: 99%